Efek Pemakaian Hormone Replacement Therapy (HRT): Systematic Review - Biomechy Oktomalio Putri; Noverial Noverial (Fakultas Kedokteran, Universitas Andalas, 2023)
Menopausal women have a risk of suffering from several diseases due to decreased levels of the hormone estrogen in the body. One effort to reduce this risk is to use Hormone Replacement Therapy (HRT). Objective: To analyzed the effect of HRT use on postmenopausal women.Methods: This research was a systematic review by searching articles in the PubMed electronic journal with keywords used [“Premenopausal women” OR “Postmenopausal women”, OR “Menopause”] AND [“Hormone Replacement Therapy” OR “Menopausal Hormone Therapy”] AND [“Increased risk disease” OR “Decreased risk disease”]. Results: There were nine studies analyzed; six studies discussed the use of HRT having a positive effect in reducing the risk of several diseases, and as many as five studies discussed the use of HRT having a negative effect, namely, it could increase the risk of several diseases. The studies discussing the factors that influence the effect of HRT use are one study discussing how to use HRT, three studies discussing the type of HRT used, two studies discussing when to start using HRT, and three studies discussing the duration of using HRT which has a significant relationship to the effect resulting from HRT use. Conclusion: The use of HRT in postmenopausal women has negative and positive effects. This effect can be influenced by how HRT is used, the type of HRT used, when HRT was started, and the duration of using HRT.Keywords: duration of use, how to use, HRT, type, time to start using